Peningkatan Kapasitas Masyarakat dalam Menggunakan Teknologi Tepat Guna Mesin Pencacah untuk Mendukung Ekowisata Desa Tempurejo Kabupaten Kediri - Santoso, Agus Muji; Istiqlaliyah, Hesty; Ramadhani, Risky Aswi; Primandiri, Poppy Rahmatika; Utami, Budhi; Budiretnani, Dwi Ari; Sulistiono, Sulistiono; Herawati, Elysabeth; Rahmawati, Ida; Sulistiyowati, Tutut Indah; Zubaidah, Siti; Okvitasari, Astri Rino; et al. (Jurnal Pengabdian UNDIKMA, 2024)
This community service activity aims to increase the community's knowledge and skills in using chopping machines, which is a basic skill in managing litter and agricultural waste into compost and processing livestock forage into silage. Service activities were carried out in Tempurejo village, Kediri Regency with a total of 36 partners. The method used in this service is an empowerment based on collaborative participation. The activity stages follow the community empowerment implementation model, namely ODSIMED (Observation, Development, Socialisation, Implementation, Monitoring, Evaluation and Desemination). The instrument used to measure community knowledge and skills is a questionnaire and the data is analyzed quantitatively. The results of this service show that partners (1) are able to determine chopped materials for making compost or silage, achieving an average skill score of 3.27, (2) are able to differentiate the function of each part of the machine, achieving an average skill score of 3.30, (3) able to turn on and turn off the machine with a partner skill score reaching 3.20, (4) able to produce various forms of shreds both for compost and silage making purposes achieving an average score of 3.50, (5) able to calculate production capacity reaching the average skill score is 3.40, and (6) being able to carry out maintenance on machines reaches an average skill score of 2.80.